Şeyh Bekir’in Şifâ’ü’l-Kulûb ve Ziyâ’ü’l-Kubûr Adlı İlmihal Eseri - Zaimovic, Nerma (FSM Vakıf Üniversitesi, 2018)
Bu makalede Şeyh Bekir’in Hicrî 1143, Miladî 1731 tarihinde yazdığı ve dinî konuları anlatan Türkçe bir ilmihâl kitabı olan Şifâ’ü’l-Kulûb ve Ziyâ’ü’l-Kubûr adlı eseri tanıtılmaktadır. Eser 10 fasıldan oluşmakta olup yazar her fasılda farklı konuları ele almış ve halkı eğitme amacı gütmüştür; yani müminlere vasiyet ve nasihat tarzında bir eser vücuda getirmiştir, diyebiliriz. Biz, bu çalışmada eseri ayrıntılı olarak tanıttıktan sonra eserde öne çıkan imlâ ve dil özelliklerini inceleyeceğiz. Böylece doktora tezi olarak incelediğimiz bu eserin Türk dili bakımından önemi bu makaleyle sahaya bir katkı olarak ortaya konmuştur.

Shifâü’l-Qulûb ve Ziyâü’l-Qubûr is an Islamic catechism in Ottoman Turkish written by Sheikh Bekir in H. 1143 (AD 1731). The present study is an analysis of this work including detailed information on the general philological features and linguistic properties of the work. The work consists of 10 chapters, and each chapter is written on a different topic that is intended to educate the public through preaching and advising about the common features and teachings of the Islam. In this work, after the introductory part on the general aspects of each chapter of the work, linguistic features of the work are presented. The findings of this article could be taken as an important contribution to the studies of Ottoman Turkish. The present article is an extended part of our doctoral thesis on the philological and linguistic aspects of the work.
General Features of the Catechism Şifâü’l-Qulûb and Ziyâü’l-Qubûr by Sheikh Bekir
Keywords: Şifâ’ü’l-Kulûb; Ziyâ’ü’l-Kubûr; Şeyh Bekir; İlmihâl kitabı; Nasîhatnâme; Osmanlı Türkçesi imlâ özellikleri; Şifâ’ü’l-Kulûb ve Ziyâ’ü’l-Kubûr; Shifâü’l-Qulûb; Ziyâü’l-Kubûr; Shifâü’l-Qulûb and Ziyâü’l-Kubûr; Sheikh Bekir; Ottoman Turkish; Islamic catechism; Ottoman religious advice and preaching; Ottoman Turkish spelling and linguistic features